2013
DOI: 10.1509/jm.11.0454
|View full text |Cite
|
Sign up to set email alerts
|

Good and Guilt-Free: The Role of Self-Accountability in Influencing Preferences for Products with Ethical Attributes

Abstract: The market share of brands positioned using ethical attributes typically lags behind brands that promote attributes related to product performance. Across four studies, the authors show that situational factors that heighten consumers' self-accountability (i.e., activation of their desire to live up to their self-standards) lead to increased preferences for products promoted through their ethical attributes. They investigate their predictions regarding self-accountability in multiple ways, including examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
347
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(375 citation statements)
references
References 56 publications
17
347
1
10
Order By: Relevance
“…There is a vast body of research focusing on lifestyle change in relation to recycling (Evans et al 2013;Sachdeva et al 2015), adopting low-carbon technologies (Skea and Nishioka 2008;Zapico et al 2009), using public transport or bicycles (Aldred and Jungnickel 2014;Schwanen et al 2012;Urry 2012) and changing diet (Mozaffarian et al 2012). Market research has revealed how preferences can be influenced (Peloza et al 2013), and paternalism and nudge theory (Thaler and Sunstein 2008;Scoccia 2013;Sunstein in press) describe how sustainable behaviour change can be promoted. In land use science agent-based models are used to incorporate individual agency in land management choices (Murray-Rust et al 2014a), and assumptions about future consumer demand feature in explorative land use scenarios (Plieninger et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a vast body of research focusing on lifestyle change in relation to recycling (Evans et al 2013;Sachdeva et al 2015), adopting low-carbon technologies (Skea and Nishioka 2008;Zapico et al 2009), using public transport or bicycles (Aldred and Jungnickel 2014;Schwanen et al 2012;Urry 2012) and changing diet (Mozaffarian et al 2012). Market research has revealed how preferences can be influenced (Peloza et al 2013), and paternalism and nudge theory (Thaler and Sunstein 2008;Scoccia 2013;Sunstein in press) describe how sustainable behaviour change can be promoted. In land use science agent-based models are used to incorporate individual agency in land management choices (Murray-Rust et al 2014a), and assumptions about future consumer demand feature in explorative land use scenarios (Plieninger et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Logically, when consumers proactively implement environmentally friendly behavior and embody the spirit of self-sacrifice, they will be certain to reap others' respect, appreciation and recognition. In addition, Peloza et al (2013) combined the study of self-standard compliance and self-discrepancy theory, proposing that the morality of sustainable behavior is an important self-standard. However, in reality, actual behavior is not always in line with this standard.…”
Section: Research Hypothesismentioning
confidence: 99%
“…These norms can be internalized in some way to satisfy oneself rather than to please others. Self-accountability was a person's desire to live up to internal selfstandards (Peloza, 2013 …”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%